Gall stone pulverisation strategy in patients treated with extracorporeal lithotripsy and follow up results of maintenance treatment with ursodeoxycholic acid. Issue 1 (January 1994) - Boscaini, M; Piccinni-Leopardi, M; Andreotti, F; Montori, A
Abstract : Between November 1988 and July 1992 70 patients with radiolucent gall stones were treated with extracorporeal lithotripsy (ESL) and ursodeoxycholic acid (UDCA; mean (SD) dose 11.2 (1.9) mg/kg/day). Fifty three patients have been followed for one year. One week after lithotripsy, 30.6% had completely eliminated all stone fragments from the gall bladder and one year later 93.9% were free of stones. Three factors were considered important in achieving these results. 'Pulverisation' of the stone–that is, its fragmentation into echogenic dust (crystalline aggregates, some few hundred mu in size) or particles similar to grains of sand, smaller than 1 mm in diameter, or both, is required. Secondly, dust and particles were rapidly eliminated, strongly suggesting a mechanical elimination process by physiological gall bladder contractions. Thirdly, there must be chemical dissolution with biliary acids. This therapeutic approach gave excellent results without causing any clinically relevant side effects. The first 20 patients who became free of stones after ESL were given oral bile acid maintenance treatment–300 mg/day of UDCA at bedtime, for two years. All were asymptomatic and none had suffered a recurrence after two years. In four patients, crystalline aggregates, detected in gall bladder bile by ultrasound, were subsequently dissolved between one and three months after resuming a full dose regimen of UDCA.